2008
DOI: 10.2137/145960610792912594
|View full text |Cite
|
Sign up to set email alerts
|

Egg performance, egg quality, and nutrient utilization in laying hens fed diets with different levels of rapeseed expeller cake

Abstract: The aim of this study was to evaluate the effect of different levels of rapeseed expeller cake (RC) in the diet of laying hens on egg performance, egg quality, retention and excretion of nitrogen, calcium and phosphorus, and metabolizability of energy. The experiment was carried out with 72 Bovans Brown hens, from 28 to 53 weeks of age. Experimental treatment consisted of four isonitrogenous and isocaloric corn-soybean diets (as calculated: 17% crude protein, 11.6 MJ/kg metabolizable energy, 0.81% lysine, 0.36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Moreover, in a study by Blair et al [ 26 ], the addition of rapeseed meals fed to Babcock hens tended to darken yolk. On the other hand, Świątkiewicz et al [ 38 ] observed slightly less colored egg yolks (about four points on the Roche scale) when Japanese quails were fed with rapeseed cake. The positive change in yolk color could also result from slightly higher crude fiber content related to the amount of rapeseed meal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in a study by Blair et al [ 26 ], the addition of rapeseed meals fed to Babcock hens tended to darken yolk. On the other hand, Świątkiewicz et al [ 38 ] observed slightly less colored egg yolks (about four points on the Roche scale) when Japanese quails were fed with rapeseed cake. The positive change in yolk color could also result from slightly higher crude fiber content related to the amount of rapeseed meal.…”
Section: Discussionmentioning
confidence: 99%
“…Although no statistical differences were found in the most important eggshell characteristics, it was seen that eggshells from groups fed with both non-fermented and fermented rapeseed meals had better quality. Therefore, rapeseed meals, especially fermented ones, probably contributed to higher calcium retention [ 38 ], preventing unfavorable changes in shell structure. This hypothesis seems to be confirmed by our research.…”
Section: Discussionmentioning
confidence: 99%
“…Glucosinolates are considered anti-nutritive factors for animal production but, on the other hand, they have an important role in plant protection against pests, diseases and also weeds (Rahmanpour et al, 2010;Haramoto and Gallandt, 2004). Originally, the rapeseed cake uses for animal feed were limited because of the presence of undesirable substances (glucosinolates, erucic acid) (Swiatkiewicz et al, 2010;Schmidt et al, 2004). Major deleterious effects of glucosinolate ingestion in animals are reduced palatability, decreased growth and production.…”
Section: Brassica Napusmentioning
confidence: 99%